Pengembangan Sistem Informasi Pengelolaan Layanan dan Keluhan (Studi Kasus: Pengelola Sistem Informasi, Infrastruktur TI dan Kehumasan Fakultas Ilmu Komputer Universitas Brawijaya) - I Gede Satya Krisna Putra; Denny Sagita Rusdianto; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The PSIK of the Faculty of Computer Science Universitas Brawijaya is in charge of handling all matters related to information systems, IT infrastructure and public relations. In carrying out its duties, PSIK has experienced several obstacles, one of these obstacles is the process of filing complaints and requests for services that are still done using forms so that it requires more time and effort in doing so. In addition, this also causes difficulties to find out the number and status of the report and the absence of parameters that indicate the level of satisfaction of the reporter. Based on the above problems, a Service and Complaint Management Information System was developed to save the time and effort needed to conduct constrained business processes. The system involves 7 actors, 67 functional needs and 1 non-functional requirement. System design produces sequence diagrams, class diagrams, database design, statechart diagrams, component design and user interface design. The Service and Complaints Management Information System is implemented into a web-based application. The Service and Complaints Management Information System is tested by unit testing, integration testing, validation testing and compatibility testing. The Service and Complaints Management Information System can assist PSIK in managing complaints reports and requests for IT services, managing their inventory and managing incoming and outgoing mail more efficiently.